2014
DOI: 10.1164/rccm.201311-2103pp
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Nucleotide-Binding Oligomerization Domain–Like Receptors in Bacterial Lung Infection

Abstract: Lower respiratory tract infections (LRTIs) are a persistent and pervasive public health problem worldwide. Pneumonia and other LRTIs will be among the leading causes of death in adults, and pneumonia is the single largest cause of death in children. LRTIs are also an important cause of acute lung injury and acute exacerbations of chronic obstructive pulmonary disease. Because innate immunity is the first line of defense against pathogens, understanding the role of innate immunity in the pulmonary system is of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 69 publications
0
28
0
4
Order By: Relevance
“…The roles of TLR2 and NOD2, their interactions, cross-regulation, and involvement with inflammatory disease have been characterized most extensively in the gut micro-environment where they serve to regulate the development of antigen-dependent colitis (Watanabe et al , 2006; Yang et al , 2007). In the lung, independent responses of TLR2 and NOD2, and their interactions with bacterial respiratory pathogens have been characterized (Yu et al , 2014; Leissinger et al , 2014). Of particular note, Davis and colleagues (2011) found that clearance of the Streptococcus pneumoniae pathogen from the upper respiratory tract was impaired only upon ablation of both TLR2 and NOD2.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of TLR2 and NOD2, their interactions, cross-regulation, and involvement with inflammatory disease have been characterized most extensively in the gut micro-environment where they serve to regulate the development of antigen-dependent colitis (Watanabe et al , 2006; Yang et al , 2007). In the lung, independent responses of TLR2 and NOD2, and their interactions with bacterial respiratory pathogens have been characterized (Yu et al , 2014; Leissinger et al , 2014). Of particular note, Davis and colleagues (2011) found that clearance of the Streptococcus pneumoniae pathogen from the upper respiratory tract was impaired only upon ablation of both TLR2 and NOD2.…”
Section: Discussionmentioning
confidence: 99%
“…Активация NLRC2 приводит к возбуждению митогенактивиру-емых протеинкиназ (MAPK) -p38, ERK 1/2 и JNK (c-Jun N-terminal kinases) -при участии адаптерной молекулы CARD9 (caspase recruitment domain family member 9) (рис. 2) [10,63,94].…”
Section: Nod-подобные рецепторыunclassified
“…Les récepteurs de l'immunité innée sont impliqués dans ce phénomène : notamment ceux de la famille des Tolllike receptors (TLR) et des NOD-like receptors (NLR). Ces récepteurs que l'on trouve soit à à la surface (TLR), soit pour certains dans le cytoplasme (NLR) de différents acteurs cellulaires des voies aériennes (cellules musculaires lisses, cellules épithéliales, macrophages), jouent un rôle majeur dans la régulation de l'immunité innée et de l'immunité adaptative, en détectant des motifs antigéniques conservés communs à certains agents microbiens bactériens et viraux (les PAMPs : pathogen-associated molecular patterns, comme le lipopolysaccharide bactérien LPS, ou les acides nucléiques exogènes) ou à certains autres motifs antigéniques constituant des signaux de danger (les DAMPs : damage-associated molecular patterns) pouvant correspondre à des particules inorganiques exogènes (polluants, certains composant de la fumée de cigarette), ou à des constituants endogènes exposés lors de la destruction tissulaire [61][62][63]. L'inactivation complète du TLR4 chez des souris knock-out provoque un emphysème précoce [64].…”
Section: Environnement Microbien Et Immunitéunclassified
“…Ces deux récepteurs jouent un rôle dans la régulation du microbiome intestinal et il pourrait en être de même pour le microbiome pulmonaire [62]. Les souris dont le gène de NOD 2 est déficient ont une clairance bactérienne diminuée [63]. NLRP3 peut être stimulé par l'acide urique, un marqueur des dommages cellulaires, et pourrait contribuer à l'inflammation bronchique via la constitution d'un inflammasome, complexe protéique déclenchant par des réactions de signalisation cellulaire en cascade la transcription d'interleukine-1bêta (IL-1␤) et de la caspase-1 conduisant au processus de pyroptose aboutissant à la mort cellulaire [62,63].…”
Section: Environnement Microbien Et Immunitéunclassified